KONSEP KERUKUNAN ANTAR UMAT BERAGAMA: Komparasi Pemikiran Jane Dammen McAuliffe dan Muhammad Abduh - Ashimuddin Musa; M. Mushthafa (Jurnal Studi Qur'an dan Tafsir, 2022)
Abstract Inter-religious harmony is one of the main pillars for the maintenance of the unity of the people and the nation. This is because creating harmony will help build a solid and harmonious life. So that people can live in peace, respect each other, appreciate equality in the practice of religious teachings, and be able to cooperate in society, nation and state. This research aims to answer two questions by using descriptive-analytical method and qualitative approach, namely What is the concept of inter-religious harmony according to Jane Dammen McAuliffe and Muhammad Abduh? And how is the concept of harmony implemented according to both perspectives? This research concludes that both Jane Dammen McAuliffe and Muhammad Abduh recognize the Qur'anic tolerance towards religious communities outside Islam to implement the law (sharia) that applies to the teachings of their religion, and the law is not produced by mutual agreement, but is self-affirmed from the teachings of the holy book of any religious community; Islam, Christianity, Judaism and others. Having said that, these two figures are not only similar but also differing. The difference can be seen from the background of these two, who have different religious backgrounds - Christianity and Islam. So when both speak or discuss their respective religions, there must be a subjective element involved, such as giving priority to each other's religions. Keywords: Inter-religious harmony, Jane Dammen McAuliffe, Muhammad Abduh